ANALISIS PERBANDINGAN AKTIVA TETAP BERDASARKAN PSAK TERHADAP LAPORAN KEUANGAN PT. MARINAL INDOPRIMA - Citra Larashati Surya; Fathorrahman Fathorrahman; Alfi Hasaniyah (Assyarikah: Journal of Islamic Economic Business, 2021)
Companies in the face of increasingly advanced business developments, a company that is founded must have a goal in order to make the company live in One form of investment is fixed assets that are used in the company's normal activities, researchers conducted a study aimed at comparing the method of depreciation of fixed assets based on PSAK against financial statements at PT. Marinal Indoprima is long term, meaning that the company must maintain its viability in achieving its goals. The research method used is descriptive quantitative research type, and the type of data used is quantitative data sourced from secondary data and primary data as well as data collection procedures through documentation. The results showed that the company has applied the method of depreciation of fixed assets based on PSAK. In its application, the company has distinguished fixed assets and how to obtain them by way of cash or credit purchases and built themselves. And the way the company assesses it considers all the costs incurred by the company to get fixed assets until they are ready for use. Represents the acquisition cost of its fixed assets, for depreciation of its fixed assets the company uses the straight-line method. And the researcher compares with the method of the number of years and the double declining balance method. With the sum of years digits method, the depreciation expense is compared with the straight-line method. Smaller the number of years, whereas with the double-declining balance method compared to by the straight line method. For the termination or disposal of fixed assets must obtain approval from the board of directors and disclosure and reporting is done at the end of the year.Â